Exporting Murder: US Deportations & the Spread of Violence - Christian Ambrosius; David Leblang (Freie Universität Berlin, School of Business & Economics, 2018)
Existing literature on cross-national variation in violence has paid little attention to the transnational transmission of crime. One such channel are the forced returns of migrants with a criminal record in their countries of temporary residence. Responding to this research gap, we study the effect of US deportations of convicts on levels of violent crime in deportees' countries of origin for a cross-country panel of up to 123 countries covering the years 2003 to 2015. We find a strong and robust effect of criminal deportations on homicide rates in countries of origin, that is to a large degree driven by deportations towards Latin America and the Caribbean. An additional inflow of ten deportees with a criminal history per 100,000 increases expected homicide rates by more than two. In addition to controlling for country-specific fixed effects, we provide evidence on a causal effect using an instrumental variable approach, that exploits spatial and time variation in migrant populations' exposure to state level immigration policies in the US.
urn:nbn:de:kobv:188-refubium-22573-7
Keywords: 330; Return Migration; Deportation; Homicide; Latin America